Retrospective study of post-treatment 131I SPECT/CT imaging for personalizing therapy of patients with differentiated thyroid cancer - Sonya Sergieva; Teodor Sofiyanski; Bozhil Robev; Milena Dimcheva; Albena Fakirova (Folia Medica)
Introduction: The absence of anatomical landmarks in the whole body scan makes it challenging to precisely localize 131I uptake, which is used to treat patients with differentiated thyroid cancer (DTC). Recently, SPECT/CT studies have been utilized to increase the diagnostic sensitivity and specificity. Aim: To evaluate the clinical role of post-treatment 131I SPECT/CT imaging in the management of DTC. Materials and methods: The study included 564 patients (384 women and 180 men) aged 12 to 83 years with DTC referred to our hospital between 2011 and 2021. A post therapeutic 131I whole-body scintigraphy (WBS) with SPECT/CT imaging was performed. Results: 370 (65%) cases with papillary carcinoma, 101 (18%) cases with follicular carcinoma, and 93 (17%) cases with follicular variant of papillary DTC were histologically proven. 131I WBS was positive in 423 (75%) cases. SPECT/CT showed thyroid remnant in 237 (42%) patients, tumor persistence – in 15 (2.7%), and local recurrence in the thyroid bad in 17 (3%) cases. Enlarged cervical and mediastinal lymph nodes were visualized in 141 (25%) cases. Forty-eight (8.5%) patients had pulmonary metastases, 14 had osteolytic bone lesions and 6 (1.4%) had brain metastases detected on the SPECT/CT images. Negative 131I SPECT/CT data influenced significantly the clinical management of a large cohort with recurrent and metastatic DTC, leading to rejection of radioiodine treatment as a therapeutic alternative. Conclusion: SPECT/CT improved the 131I WBS accuracy, thus changing the management of DTC determining indications for surgery, the need to give or withhold 131I therapy, and selecting cases for radiotherapy or chemotherapy in order to personalize the treatment.